Ethical Use of Technology in Digital Learning Environments Graduate Student Perspectives - Brown, Barbara; Roberts, Verena; Jacobsen, Michele (Open textbook library., 2020)
This book is the result of a co-design project in a class in the Masters of Education program at the University of Calgary. The course, and the resulting book, focus primarily on the safe and ethical use of technology in digital learning environments. The course was organized according to four topics based on Farrow’s (2016) Framework for the Ethics of Open Education.